Socio-psychological factors explaining public engagement and support for drought disaster risk management - Areia, Neide P.; Sequeira, Mário D.; Tavares, Alexandre O. (International journal of disaster risk reduction, 2024)
Droughts have become a critical high-impact hydro-meteorological disaster and are projected to become more extreme in the near future. The Iberian Peninsula is unarguably considered a pronounced hot spot for drought. Worrisome projections for drought risk come to emphasize the urgency of building drought-resilient societies, through integrated risk management processes that bring together all societal spheres, including lay citizens. However, citizens remain disengaged from climate risk and adaptation processes. Therefore, it is critical to understand how societies respond to climate-related hazardous processes, such as drought, and to determine the predictors of citizens' engagement in disaster risk management. To respond to this research need, this study sought to explore citizens' preferences for drought management policies and to ascertain the psychosocial predictors of citizens' willingness to take action towards drought and support for drought risk management. A cross-sectional study was implemented, in which 401 Portuguese participants enrolled in a survey questionnaire measuring predictor variables of citizens' willingness to take action and support for drought risk management. A robust set of statistical analysis was implemented, mainly based on structural equation modelling. Results demonstrate that citizens tend to prefer low-cost measures and policies that due not imply personal heightened burden, at a financial and behavioral level. Moreover, personal experience with drought, risk perception, perceived urgency and emotional states play a critical role in citizens’ engagement and support for disaster risk management. Findings are discussed in light of their theoretical and practical implications, particularly for risk communication and for risk management policymaking. [Display omitted] •Droughts are becoming critical high-impact hydro-meteorological hazards in Europe.•Personal experience with drought predicts support for drought risk management.•Urgency and risk perception are key predictors of support for drought risk management.•Emotions play a critical role in individuals' engagement in drought risk management.•Citizens demonstrate higher preference for low-cost drought risk management policies.